REALITAS SOSIAL MINANGKABAU DALAM PERTUNJUKAN TEATER “CADIK PATAH” - Fitri Noveri; Koes Yuliadi; Sahrul Sahrul (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
ABSTRACT Cadik Patah play is a play inspired by Minangkabau people’s reality in West Sumatra highland namely Lima Puluh Kota district. This search is inspired from many domestic conflicts occurred in Minangkabau as the result of kinship pattern in the household namely conflict happened between married children’s families with their parents (parents in law) as the result of the existence of several household heads in one nuclear family.Besides being inspired by those things above, Cadik Patah play is also materialized into tragicomedy drama namely the combination of tragedy drama and comedy-drama. The content of its story consists of sadness and humor/jokes that entertain audiences. Story told has serious conflict and funny humorous scenes that decrease tension. In the following scene, the tension of story conflict improves so drama becomes more exciting and attractive and then the audiences want to enjoy it continuously.Cadik Patah script is then believed to take hyperrealist style. Hyperrealist intended by the authors is that in the making of this drama, authors will look for objects that are interesting in object material itself. Although this style is influenced by instrumental theater or environmental theater, it can be observed that both of them have differences. If instrumental theater is the theater inspired by ritual or it uses available instruments, the style called as hyperrealist by the author still applies the strict arrangement of the dramatic plot like in realist plays. It is just that the author tries to explore the smallest object into an interesting theme to be discussed by characters in Cadik Patah play. Keywords: Drama, Cadik Patah, Social Reality, Tragicomedy.